Analysis of Muhammadiyah Ideology on the Performance of Muhammadiyah Primary and Secondary Education Institutions with Leadership as Mediation - Safiq Abdillah; Setyo Budi; Mahjudin Mahjudin (Budapest International Research and Critics University, 2023)
This study aims to determine the effect of Muhammadiyah ideology on the performance of Muhammadiyah Elementary and Secondary Education institutions with Leadership Variables as Mediation, using a quantitative approach method and with a population of 1607 people, the research sample was obtained as many as 469 people. Gresik district. The results showed that leadership had an effect on the performance of educational institutions. Where leadership can improve the performance of educational institutions with the most prominent character of hard work and leadership has a competitive mediation role. Where the leadership between Muhammadiyah ideology and the performance of educational institutions has a significant impact.